The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s12935-020-01221-y
|View full text |Cite
|
Sign up to set email alerts
|

A long non-coding RNA LINC00461-dependent mechanism underlying breast cancer invasion and migration via the miR-144-3p/KPNA2 axis

Abstract: Background: The purpose of this study was to explore the regulatory mechanism of the long non-coding RNA (lncRNA) LINC00461 underlying the breast cancer invasion and migration via the miR-144-3p/KPNA2 axis. Methods: Bioinformatics methods were applied to screen differentially expressed mRNAs, miRNAs and lncRNAs for construction of a competing endogenous RNA (ceRNA) network. LINC00461, KPNA2 and miR-144-3p were identified, and KPNA2 was predicted to be a target of miR-144-3p and significantly correlated with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Due to the frequent occurrence of bone metastasis in patients with advanced breast cancer, the understanding of pathogenesis and clinical management of bone metastasis are important and challenging topics in basic research and clinical practice. The ceRNA network, including mRNA, miRNA, and lncRNA, and infiltrating immune cells may be critical to further understand this phenomenon [17] , [18] , [19] , [20] . We observed that tumour samples with bone metastasis had significantly altered proportions of infiltrating cells compared with breast cancer without bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the frequent occurrence of bone metastasis in patients with advanced breast cancer, the understanding of pathogenesis and clinical management of bone metastasis are important and challenging topics in basic research and clinical practice. The ceRNA network, including mRNA, miRNA, and lncRNA, and infiltrating immune cells may be critical to further understand this phenomenon [17] , [18] , [19] , [20] . We observed that tumour samples with bone metastasis had significantly altered proportions of infiltrating cells compared with breast cancer without bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA is a type of ncRNA with over 200 nucleotides, which is not related to protein-coding [17] , [18] , [19] , [20] , [21] . New evidence suggests that lncRNA imbalance occurs frequently in many malignant tumours, which is a key factor for carcinogenesis through post-transcriptional regulation and epigenetic modification [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the frequent occurrence of bone metastasis in patients with advanced breast cancer, the pathogenesis and clinical management of bone metastasis are important and challenging topics in basic research and clinical practice. The ceRNAs network, including mRNA, miRNA, and lncRNA, and immune cells that in ltrate the tumour may be critical to further understand this phenomenon [12][13][14][15]. We observed that tumour samples with bone metastasis had signi cantly altered proportions of in ltrating cells compared with breast cancer without bone metastasis.…”
Section: Discussionmentioning
confidence: 85%
“…Lncrna is a type of ncRNA with over 200 nucleotides, which has nothing to do with protein-coding [12][13][14][15][16]. New evidence suggests that lncRNA imbalance occurs frequently in many malignant tumours and are vital for carcinogenesis through post-transcriptional regulation and epigenetic modi cation [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation